Sequential two-step fractionation of lignocellulose with formic acid organosolv followed by alkaline hydrogen peroxide under mild conditions to prepare easily saccharified cellulose and value-added lignin. (15th September 2017) - Li, Ming-Fei; Yu, Ping; Li, Shu-Xian; Wu, Xiao-Fei; Xiao, Xiao; Bian, Jing
Graphical abstract: Highlights: Atmospheric pressure pretreatment was developed for a second-generation biofuel. The pretreatment media were formic acid and alkaline H2 O2 aqueous solution. Pretreatment caused effective removal of recalcitrant components. A high conversion rate of cellulose into glucose (99.36%) was achieved. The lignin obtained exhibited great potential to produce liquid fuel. Abstract: For the production of the second generation bioethanol, enzymatic saccharification to prepare a high yield of fermentable sugars is an essential step for the conversion of energy from lignocellulose. In this case, a mild two-step pretreatment using anhydrous formic acid and alkaline hydrogen peroxide aqueous solution was developed to fractionate lignocellulose to highly digestible cellulose for enzymatic saccharification as well as value-added lignin. Bamboo was pretreated with anhydrous formic acid at 40–100 °C for 4 h and then extracted with alkaline hydrogen peroxide aqueous solution (containing 1% NaOH and 1% H2 O2 ) at 80 °C for 2 h. The lignin dissolved in anhydrous formic acid was isolated and further treated with the alkaline solution obtained from the pretreatment and then recovered. The produced cellulose residue had a rather high conversion rate of cellulose into glucose (99.36%) under an enzymatic hydrolysis for 72 h. In addition, the lignin obtained preserved good functionalities, which exhibited great potential to produce liquid fuels, thus implementing the philosophy of biorefinery. The results indicated that the two-step formic acid-alkaline hydrogen peroxide pretreatment effectively broke the recalcitrant nature of lignocellulose, producing a good feedstock for the conversion into energy.